Socio-Economic Impact of Financing Facility on Low-income Communities and Developers in Indonesia - Widyastutik Widyastutik; Sri Retno Wahyu Nugraheni; Fahmi Salam Ahmad; Kurniawan Khristianto; Yenni Nur 'Aini (Signifikan: Jurnal Ilmu Ekonomi, 2022)
Housing financing is one of the essential solutions to make it easier for people to access the need for livable houses. One of the subsidy schemes from the government is the Housing Financing Liquidity Facility (FLPP) by BLU PPDPP. This study focuses on the socio-economic impact of FLPP at the micro level for low-income communities (MBR) and developers. Two econometric approaches are used to analyze: one-way t-tests and linear regression analyses. The analysis results show the impact of FLPP on the micro level for MBR and developers provides a better improvement in welfare. The developer company that distributes FLPP has an increase in welfare from various aspects such as demand for housing units, company image, and company assets. For MBR, there are improvements in terms of income, education, health, work, and other supporting infrastructure.How to Cite:Widyastutik., Nugraheni, S. R. W., Ahmad, F. S., Khristianto, K., & Aini, Y. N. (2022). Socio-Economic Impact of Financing Facility on Low-Income Communities and Developers in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 219-238. https://doi.org/10.15408/sjie.v11i2.26589.